(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to explain blended learning and learning styles towards students’ conceptual understanding. This study was designed as a quasi-experiment involving 84 students of the IslamicsEducation Department, Faculty of Education of Islamics Institute of Al-KhairatPamekasan, Indonesia. The research data were collected using a test. Before the study, tests were carried out for the experimental and control groups. Data were analyzed using descriptive statistics and ANOVA test with pre-test scores as covariates. The level of significance was determined at α = 0.05. The results showed that (1) there were differences in learning outcomes between those taught with the blended learning model and those taught with the conventional learning model. (2) The difference in learning outcomes between groups of students who had to learn styles and groups of students with low learning discipline. Student learning discipline had an essential role in the learning process. These findings indicated that blended learning could dominate the learning outcomes of students’ conceptual mastery. Future research might be able to discuss the results of tests conducted to determine the effectiveness of mastery of learning concepts with other learning models.